Efektifitas Psikologi Kerekayasaan Tata Ruang Kerja Terhadap Motivasi Kerja Karyawan Gravure Production di PT XYZ - Jeklin Darsono Sidebang; Arif Rahman Hakim; Regi Ramadan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the effectiveness of workplace design psychology in improving employee motivation at PT XYZ. The approach used is a quasi-experimental quantitative method with a Two-Group Pretest-Posttest design. The research sample consists of 60 employees from the gravure production division, divided into two groups: the experimental group and the control group. Data collection was conducted using a work motivation scale based on Herzberg's theory(1966). Pretest and posttest results were analyzed using the independent sample t-test and gain score test. The research findings indicate that the experimental group experienced a significant increase in work motivation after the intervention, with a t-test value of 4.040 (p < 0.001) and an effect size of 38.56%. Thus, this study proves that the application of workplace ergonomics psychology is effective in enhancing employee work motivation, thereby accepting the alternative hypothesis (Ha).